Între «descriptio» și «naratio» sau despre constituenții determinanți ai structurii textelor lui Calistrat Hogaș, Ion Creangă și Barbu Ștefănescu Delavrancea - Dorin Sergiu Ursuț (Revista de Istorie și Teorie Literară)
The article titled Between “Descriptio” and “Narratio” or on the Determinant Constituents of the Structure of the Works of Calistrat Hogaș, Ion Creangă and Barbu Ștefănescu Delavrancea explores in detail the relationship between description („descriptio”) and narration („narratio”) in Romanian prose, focusing on the works of Calistrat Hogaș, Ion Creangă and Barbu Ștefănescu Delavrancea. Although description has been traditionally considered secondary to narration, with a vaguer role and often seen as a „pause” in the storyline, it remains a crucial constituent of the literary text’s structure. In the prose of Calistrat Hogaș, Ion Creangă and Barbu Ștefănescu Delavrancea, description plays a central role, being rich in technical vocabulary, proper names, metaphors, synecdoches, and other rhetorical figures. Descriptions become veritable „lists” of details, contributing to the creation of a specific rhythm. For example, Creangă’s descriptions, whether of peasant houses or natural landscapes, are filled with details and stylistic figures, creating a „reality effect” and deepening the reader’s engagement. Hogaș, on the other hand, uses description to create contrast between characters and their environment, while Delavrancea employs description in a rhythmic and intense way, creating a tense and uneasy atmosphere in his short stories.